Association of Blood Lipids, Non-HDL-Cholesterol and Lipid Ratios with Early Onset Myocardial Infarction in a Bangladeshi Population (Journal of Medicine, 2009)
Objective- To explore the status of blood Lipids, non-HDL-Cholesterol and Lipid Ratios in early onset Myocardial Infarction in a Bangladeshi population. Design- A case control study involving 50 early onset Myocardial Infarction patients as cases (age < 45 years) and 50 late onset MI patients as control (age > 60 years). It was carried out from January 2006 to December 2007 in the Department of Biochemistry, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. Results- Serum Total cholesterol, Triacylglycerol and TAG/TC ratio found significantly raised in cases compared to controls; but with respect to Low Density Lipoprotein-cholesterol ( LDL-C), High Density Lipoprotein-Cholesterol(HDL-C), non-HDL-C, TC/HDL-C ratio, LDL-C/HDL-C ratio cases & controls found to be identical. Conclusion - Hypercholesterolemia and hypertriglyceridaemia are associated with early onset Myocardial infarction. doi: 10.3329/jom.v10i2.2819 J MEDICINE 2009; 10 : 82-85